2023
DOI: 10.1021/acsami.3c13242
|View full text |Cite
|
Sign up to set email alerts
|

X-ray and UV Irradiation-Induced Reactive Oxygen Species Mediated Antibacterial Activity in Fe and Pt Nanoparticle-Decorated Si-Doped TiCaCON Films

Viktor A. Ponomarev,
Alexander N. Sheveyko,
Konstantin A. Kuptsov
et al.

Abstract: Bone implants with biocompatibility and the ability to biomineralize and suppress infection are in high demand. The occurrence of early infections after implant placement often leads to repeated surgical treatment due to the ineffectiveness of antibiotic therapy. Therefore, an extremely attractive solution to this problem would be the ability to initiate bacterial protection of the implant by an external influence. Here, we present a proof-of-concept study based on the generation of reactive oxygen species (RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 78 publications
1
2
0
Order By: Relevance
“…It was previously shown that the surface of Cu-doped PEO coatings generates ROS after UV irradiation . A comparison of the effects of UV and X-ray irradiation on the surface of metal nanoparticles-decorated TiCaCON–Si coating showed that the maximum ROS concentration after short-term soft X-ray irradiation was significantly higher than after long-term UV irradiation . The effect of X-ray irradiation on ROS generation by the PEO surface has not been studied previously.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…It was previously shown that the surface of Cu-doped PEO coatings generates ROS after UV irradiation . A comparison of the effects of UV and X-ray irradiation on the surface of metal nanoparticles-decorated TiCaCON–Si coating showed that the maximum ROS concentration after short-term soft X-ray irradiation was significantly higher than after long-term UV irradiation . The effect of X-ray irradiation on ROS generation by the PEO surface has not been studied previously.…”
Section: Resultssupporting
confidence: 60%
“…These changes in the band structure affect the material photochemical properties, promote the indirect transfer of electrons from the valence band to the conduction band, and prevent rapid charge recombination . X-ray irradiation-induced ROS-mediated antibacterial activity was recently reported for metal nanoparticles-decorated TiCaCON–Si films, but for the PEO coating, it is observed for the first time. In conclusion, we would like to highlight the important difference between our experiments, in which PEO-Zn coatings were exposed to UV and X-ray irradiation before being placed in cell culture, compared to UV irradiation of an Ag-containing Ti sample simultaneously with bacteria, which resulted in an enhanced bactericidal effect due to hydroxyl radicals generated from the bacterial cell .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation